Japanese young people’ perceptions of Russia - Larisa Vladimirovna Zhilina (Vestnik RUDN. International Relations, 2018)
This paper explores the dynamics of changing perceptions of Russia by Japanese young generation. The aim of the paper is to examine attitude toward Russia among young Japanese people, and to investigate factors that affect their “distant neighbor” perceptions and attitudes, and how it has changed within five years. As relations between Japan and Russia grow more complex, the need for more knowledge for mutual understanding is getting great. It is based on a series of more detailed data analyses of the polls conducted at the Universities of Japan - as a part of research project “Student’s Representations of neighboring countries at the beginning of 21st century - Russia and Japan”. In the research author turned to a student’s audience, which is most perspective for acting with, on the way of creation of public opinion about foreign countries as well. Author address ﬁndings that obtained in 2007 and 2012 and use qualitative research methods, such as interviewing and discourse analysis. So, we provide an overview of findings from representative surveys and analyze findings from studies to draw conclusions about the drivers of changing public perceptions towards Russia. Presented research is an illustrative explanation - stereotyped images are long-lasting and durable. They are difficult to change and can be passed on as heritage from the past. Author concludes that although in general at the level of the University students’ perceptions towards Russia have not been changed, but in details we can see some quantitative changes. The results indicated that some Japanese students held quite optimistic opinions toward Russia, but there was also evidence that public opinions toward Russia differed across the students and sometimes not in positive way.